ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUH NASABAH MELAKUKAN DEPOSITO MUDHARABAHPADA BANK ACEH SYARIAH CABANG PEMBANTU IDI RAYEUK - febi febi; Muhammad Dayyan; Early Ridho Kismawadi; Muliana Muliana (JIM: Jurnal Ilmiah Mahasiswa, 2019)
AbstractThis study aims to determine the factors that affect customers to deposit mudharabah at Aceh Sharia Bank Idi Rayeuk Branch and to determine the partial and simultaneous effect on interest in mudharabah deposits. There are several factors that influence customers in performing mudharabah deposits such as the influence of profit sharing factors, service factors and promotion factors. This study is quantitative study, using 81 respondents as research sample. Sampling in this research is done by probability sampling with Random sampling method, that sample selection technique without considering the level that exist in that population. Data collection techniques using questionnaires as many as 41 items of questions assessed by the likert scale 1-5 and tested its feasibility using the validity and realiability test. The collected data were classical assumption test including multicolinearity test, heterokedasticity, normality, autocorrelation and linearity. To analysis data using multiple regression with determination test method, F test and t test. Based on multiple regression analysis at significance level 5% showed that simultaneously factor of profit sharing, service factor and promotion factor have a significant positive effect to make decision to do mudharabah deposit. The results also show partially that (1) there is a significant positive effect of profit sharing factor to make decision to do deposit mudharabah at Aceh Sharia Bank Idi Rayeuk Branch; (2) there is a significant positive effect of service factor to make decision to do deposit mudharabah at Aceh Sharia Bank Idi Rayeuk Branch; and (3) there is a significant negative effect of profit sharing factor to make decision to do deposit mudharabah at Aceh Sharia Bank Idi Rayeuk Branch. The service factor variable has the most dominant influence with significance (0,000 <0.05) and tcount> ttable (4,518> 1,991).